Pengaruh Neurokognitif Umpan Balik Visual Tertambah terhadap Pembelajaran Keterampilan Handspring Belakang dalam Senam pada Mahasiswa Berbagai Metode Pembelajaran - Maysaa Ridha Ghanim (Indonesian Journal of Physical Education and Sport Science, 2025)
Study purpose. This study examines the impact of enhanced visual feedback on learning the back handspring in gymnastics among female students, focusing on the interaction between learning styles (visual, auditory, sensory/kinesthetic) and performance improvement. Materials and methods. Thirty second-year female students were divided into three groups based on their learning style (visual, auditory, sensory/kinesthetic). The study used the VARK scale, EMG device for muscle response measurement, slow-motion video for visual feedback, and performance evaluation forms. Pre- and post-tests were conducted, with feedback tailored to each group's learning style. Results. Significant improvements were observed in all groups. The Visual Group showed the highest improvement (p < 0.01), followed by the Kinesthetic Group (p < 0.01), and the Auditory Group (p < 0.05). ANOVA revealed significant differences between groups (p < 0.01). The Visual and Kinesthetic Groups showed an inverse relationship between response time and performance accuracy, while the Auditory Group did not. Conclusions. The study concluded that visual feedback significantly enhances motor skill learning, particularly for visual learners. Sensory feedback also contributed to performance improvement. The Visual Group showed the best results, highlighting the importance of aligning teaching methods with learning styles for optimal performance. EMG data confirmed that visual and sensory feedback improves neuromuscular response speed and accuracy.